Small Radial Compressors: Aerodynamic Design and Analysis - K. A. R. Ismail; C. V. A. G. Rosolen; F. J. Benevenuto; D. Lucato (International Journal of Rotating Machinery)
This paper presents a computational procedure for the analysis of steady one-dimensional centrifugal compressor. The numerical model is based on the conservation principles of mass, momentum and energy, and has been utilized to predict the operational and aerodynamic characteristics of a small centrifugal compressor as well as determining the performance and geometry of compressor blades, both straight and curved.